Benefit of Nigella sativa for Chronic Obstructive Pulmonary Disease Patients: A Narrative Review - Sandy Laveda; Wayan Wahyu Semara Putra; Tungki Pratama Umar (Jurnal Respirasi, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory disease that has a significant global impact. Unfortunately, current treatments and prevention remain insufficient. Nigella sativa (NS) has been traditionally used as an anti-inflammatory, antioxidant, and immunomodulatory agent, which can be helpful in the treatment of COPD, through its essential component thymoquinone. This review examined the potential benefits of NS for COPD patients as a possible treatment option. Methods: The literature investigation was conducted by searching relevant articles on Google Scholar and NCBI using the keywords "black seed", "black cumin”, "Nigella sativa", "thymoquinone", "carvacrol", and "COPD". The results from five identified studies were then summarized. Results: This review reveals that NS offers benefits to individuals with COPD by reducing inflammation and oxidative stress, thereby leading to improved pulmonary function tests (PFTs). However, it is important to note that the majority of experiments have been conducted on animals, with only one involving humans, and these experiments have mostly been short-term. Additionally, since different studies have used various preparations of NS, determining the recommended dose is challenging. Unfortunately, the research does not provide any insights into the potential long-term effects of these treatments or the possible adverse effects of the medications used. Conclusion: Studies on the benefits of NS as an anti-inflammatory and antioxidant for COPD adjuvant therapy show promising results, but more research is needed to confirm the findings with larger and more well-designed studies to determine the appropriate doses and long-term effects.